MOSCOW CONTEMPORARY Museen zeitgenössischer Kunst im postsowjetischen Russland - Bayer, Waltraud M. (Mandelbaum Verlag, 2016)
The monograph is the first international study to analyze and describe the process of the post-Soviet contemporary art museums from 1992 to 2015. Based on exemplary case studies, it covers the heterogeneous museum-political development, both on the state as well as on the local Moscow level. In addition, it offers a comprehensive documentation of analogous and digital sources.